Peran Hak Kekayaan Intelektual dalam Meningkatkan Perlindungan Karya Kreatif di Indonesia - Ayunistia, Sinta; Armansyah, Rian; Badru, Ujang (UNIVERSITAS SERAMBI MEKKAH, 2025)
The protection of creative works through Intellectual Property Rights (IPR) is crucial for regulating the use of creative works in Indonesia, especially with the rapid development of the creative industry, which encompasses sectors such as music, film, visual arts, design, and technology. IPR protection is necessary to safeguard the rights of creators from misuse or piracy and to provide incentives for creators to continue innovating. This study aims to analyze the intellectual property regulations in Indonesia and identify the challenges in their implementation. The research uses a normative approach with a descriptive-analytical method to examine the relevant laws, such as the Copyright Law, Patent Law, and Trademark Law, as well as related legal doctrines. The findings indicate that although existing IPR regulations are adequate, their implementation is hindered by low public awareness of the importance of registering creative works and the weak enforcement of IPR, particularly in the case of online piracy. Based on these findings, the study recommends more intensive public education on IPR protection, as well as simplifying the registration process to make it more accessible and affordable. Furthermore, strengthening the enforcement of IPR violations is essential to create more effective protection for creative works in Indonesia.